Integrierte Roboterentwicklung für die Pflege: Konzeptionelle und praktische Herausforderungen am Beispiel ReThiCare - Andreas Bischof; Eva Hornecker; Philipp Graf; Lena Franzkowiak (TATuP – Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis, 2022)
Innovation agendas for care are increasingly flanked by demands for participatory and transdisciplinary approaches. However, especially in care robotics, it is difficult to shift the focus to early involvement of people and lifeworlds. We present the integrated methodology of a care robotics project and introduce inter- and transdisciplinary steps that help open up the development process even in an early project phase and adapt goals for robotic concepts to needs. We then discuss these steps in terms of their conceptual and practical research challenges.